Conformational flexibility of metalloporphyrins studied by density-functional calculations - Wölfle, Thorsten; Hieringer, Wolfgang; Görling, Andreas (Physical Chemistry Chemical Physics, 2008)
Reliable energetic data on the conformational flexibility of organic molecules are important ingredients to better understand the adsorption of such molecules on solid surfaces. Herein, the conformational flexibility of the phenyl substituents in metallo tetraphenyl porphyrins (M-TPP, M = Zn, Co) and metallo tert-butyl tetraphenyl porphyrins (M-TTBPP, M = Zn, Co) has been studied in detail for the first time using density-functional methods. For each molecule, a relaxed two-dimensional potential energy surface scan has been calculated for the two angles describing the rotation and the out-of-plane bending of the phenyl substituents. The results quantify that the molecules are rather flexible close to the energetic minimum while more extreme twisting or tilting of the phenyl substituents results in high-energy deformations of the porphyrin core from planarity due to steric repulsions of adjacent hydrogen atoms. © the Owner Societies.